2021
DOI: 10.2903/j.efsa.2021.6970
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Opinion of the Scientific Panel on Plant Protection Products and their Residues (PPR Panel) on testing and interpretation of comparative in vitro metabolism studies

Abstract: EFSA asked the Panel on Plant Protection Products and their residues to deliver a Scientific Opinion on testing and interpretation of comparative in vitro metabolism studies for both new active substances and existing ones. The main aim of comparative in vitro metabolism studies of pesticide active substances is to evaluate whether all significant metabolites formed in the human in vitro test system, as a surrogate of the in vivo situation, are also present at comparable level in animal species tested in toxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 106 publications
0
31
0
Order By: Relevance
“…Comparative in vitro metabolism studies have been developed using specific mammalian cell types, e.g. hepatocytes (EFSA PPR Panel Opinion, 2021b). Similarly, OECD guidance on the determination of clearance of chemicals in rainbow trout cell lines is also available (OECD, 2018a).…”
Section: Effect Assessment Tiers Used In the Risk Assessment By Apply...mentioning
confidence: 99%
“…Comparative in vitro metabolism studies have been developed using specific mammalian cell types, e.g. hepatocytes (EFSA PPR Panel Opinion, 2021b). Similarly, OECD guidance on the determination of clearance of chemicals in rainbow trout cell lines is also available (OECD, 2018a).…”
Section: Effect Assessment Tiers Used In the Risk Assessment By Apply...mentioning
confidence: 99%
“…Moreover, for many chemicals, there are significant differences in metabolism between rats and humans, and only rat S9 microsomes are used to produce metabolic transformation in the OECD genotoxicity TGs. In a recent European Food Safety Authority (EFSA) scientific panel opinion paper relating to the toxicological testing of pesticides, the use of in vitro human metabolite data is recommended to identify any potential human relevant metabolites that had not been adequately tested in non-human toxicological studies ( EFSA 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…The comparative in vitro metabolism study using liver microsomes from F344/DuCrl Rats, Beagle Dogs and Human indicated no significant differences between animal laboratory species and human liver microsomes. EFSA noted that the study does not follow the recent recommendations of the EFSA Panel on Plant Protection Products and their Residues (PPR) Opinion on comparative in vitro metabolism studies (EFSA PPR, 2021 ).…”
Section: Mammalian Toxicologymentioning
confidence: 99%